Calculating the electronic transmission properties of semiconducting carbon nanotube Schottky diodes with increase in diameter - Rashid Nizam; S. Mahdi A. Rizvi; Ameer Azam (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Transmission of twenty-four carbon nanotube geometries to form twelve intramolecular junctions between every two carbon nanotubes have been investigated numerically. The twelve carbon nanotubes are zigzag and rest carbon nanotubes are armchair forming three different kinds of intramolecular junctions named as circumferential defective carbon nanotubes, grouped defective carbon nanotubes and distributed defective carbon nanotubes. Electronic states joining carbon nanotubes form Schottky diode that is analyzed using the tight-binding method. These quantum transmissions through Schottky diodes have been compared among the different defective carbon nanotubes and correlated with the pentagon and heptagon that formed in the intramolecular junction. The transmission coefficient of conduction band always simulated less than the transmission coefficient of valence band in each intramolecular junction irrespective of the joining of carbon nanotubes in the Schottky diodes. The maximum asymmetry of distributed defective carbon nanotubes in transmission is observed more clearly than that for other two defective carbon nanotubes forming Schottky diodes. It is interesting to note that the position of the localized states above and below the Fermi energy level may be controlled with the distribution of the defect pairs and the hexagons around the defects in the defected carbon nanotube.